Dari Tembokan ke Sorjan: Sejarah Perkebunan Jeruk Martapura dalam Lanskap Lahan Basah Banjar - daud Yahya; lita luthfiyanti; Heri Susanto (UNIVERSITAS MUHAMMADIYAH METRO, 2027)
This article analyzes the history of Martapura-Sungai Tabuk citrus cultivation as a wetland agrarian landscape of Banjar. Using historical method through heuristics, source criticism, interpretation, and historiography, the study combines Donicie's 1942 colonial agronomic report on djeroekcultuur in Bandjermasin-Marabahan and Martapoera with colonial maps, local historical studies, 1992 agribusiness data, contemporary reports on Sungai Tabuk citrus revitalization, and Banjar Regency in Figures 2026. The findings show that Martapura citrus was not merely a horticultural commodity, but an agrarian archive of community adaptation to swamps, lakes, rivers, tembokan, sorjan, trade networks, and changing cultural taste. BPS 2026 data confirm that Sungai Tabuk remains an important producer of siam/keprok citrus in Banjar Regency. The article's novelty lies in reading citrus as a bridge between wetland technology, village economy, trade networks, and Banjar taste memory.